To find the total increase, we will subtract -14 from 36.
36--14=50
(A double negative is a positive.)
50 is your final answer.
Answer:
23
Step-by-step explanation:
In this question, we want to evaluate the expression "9z-4" for z=3.
This means, we want to calculate the result when we substitute the z in this expression for 3.
So we have: 9(3)-4, which is equal to 23.
Let me know if this helps!
Can you upload another picture, you cannot really see your problem
Basiclaly solve for y
8x+4y=16
minus 8x both sides
4y=-8x+16
divide by 4 both sides
y=-2x+4